Herpes zoster during the COVID-19 pandemic - Olga Krupa; Aleksandra Małolepsza; Anna Woźniacka (Termedia Publishing House, 2022)
Varicella-zoster virus leads to primary infection, i.e. varicella, and remains in latent form in sensory dorsal root ganglion cells. Further replication and manifestation of skin lesions characteristic for herpes zoster may occur many years later. Primary cutaneous eruptions are blisters, filled with serous content, grouped on an erythematous area, merging into larger blisters. The virus reactivates most often in elderly people, people with impaired immunity, as well as those undergoing radiotherapy or excessive exposure to UV radiation. Recently, many studies indicate a relationship between SARS-CoV-2 and reactivation of varicella- zoster virus. It is suggested that skin lesions characteristic for herpes zoster can be the first sign of COVID-19, can coexist with SARS-CoV-2 infection or can appear after recovery.